A STUDY ON THE EXPENDITURE PATTERN OF WOMEN WORKERS IN METRO CHENNAI - B, NAINAR (International Journal of Psychosocial Rehabilitation, 2020)
Consumption means the final use of goods and services to satisfy human wants, needs and desires. It is a process of deriving utility from goods and services. People belonging to different classes of income have different structures of consumption. Economic Development not only brings about significant changes in the socioeconomic and cultural life of a habitant population but it also influences the levels of living in the long run. Increasing number of working women, rise in the per-capita income in forcible situations of other dominants, changing lifestyles and increasing level of prosperity of the surroundings with lack of saving attitude and appropriate awareness brought a significant changes in the expenditure patterns.(Philip Musgrove (1985), Against this background this study aims to explore expenditure pattern of unorganized women workers in Metro Chennai city. Multi-stage sampling design was adopted for selecting the sample which was restricted only to urban slums in Metro Chennaiand making a total sample size of 600 women. The study found that majority of the women workers spend major portion of their income on food and towards rent for their houses. The women workers spend 10 percent on health. Most of the women workers in these groups had saving habit. Consumption expenditure on non-food items as a percentage of total expenditure is the highest for this group. The low wages and untimely payment too have added to the financial burden on the women workers.